Descriptive Analysis of Long Pass Results in Football Games - Marsyanurdin, Muh; Kristina, Putri Cicilia; Putri, Siti Ayu Risma (Yayasan Sembilan Pemuda Indonesia, 2023)
The low results of students' long pass at the BBSA soccer school cannot be separated from the training process that is being held. The purpose of this research is to increase the long pass results of BBSA Betung soccer school students through plyometric exercises through a demonstration approach. Implementation of the long pass with plyometric training through the demonstration method approach, is to follow the five stages of the demonstration cycle, namely ask (ask), invest (investigate), create (produce), discuss (discussion), and reflect (reflection). The research method used is the research method. This research is included in experimental research using sports action research (PTO) or commonly called PTK with actions carried out in two cycles. The research instruments used were pre-test/post-test sheets and educators/students. The research subjects were 18 BBSA football school students. The results showed that the results of plyometric training had increased after applying plyometric training through a demonstration approach. The results of the ability of the BBSA football school students to practice plyometrics using the demonstration approach increased.